Variation in Dynamics, Controls, and Impacts of Agulhas Leakage through Late Pleistocene: A Review - Verma, Divya; Govil, Pawan; Kumar, Brijesh; Khan, Hidayatullah (Journal of Palaeosciences, 2023)
The Indian–Atlantic water exchange that occurs south of Africa, commonly known as the Agulhas Leakage, is a significant component of global ocean circulation. Apart from supplying warm, saline water to the South Atlantic, the Agulhas Leakage plays an essential role in the global thermohaline circulation. Variations in leakage cause changes in the strength of Atlantic meridional overturning and oscillations in the formation of North Atlantic Deep Water (NADW). This review paper attempts to understand better the dynamics of the Southern Hemisphere’s Agulhas Leakage based on various proxies. The first aspect of this paper concentrates on planktonic foraminifera and other proxies–based reconstruction of the strength of paleo Agulhas Leakage. Secondly, the emphasis would be placed on the controls of the Agulhas Leakage, its impact and its linkage with the Indian Summer Monsoon (ISM). The interactions between the fluctuating westerlies in the Southern Hemisphere, the Subtropical Front (STF) and the Indian Summer Monsoon may affect the variability of Agulhas Leakage. During glacial terminations and following interglacial periods, there is a notable intensification of leakage, which subsequently enhances the Atlantic Meridional Overturning Circulation (AMOC) and assumes a pivotal function in the global transportation of heat. By synthesizing current knowledge, this review highlights the need for further research to better understand and predict the ramifications of Agulhas Leakage in the face of a changing climate.